2011
DOI: 10.1007/s10534-011-9410-0
|View full text |Cite
|
Sign up to set email alerts
|

In silico modeling of the Menkes copper-translocating P-type ATPase 3rd metal binding domain predicts that phosphorylation regulates copper-binding

Abstract: The Menkes (ATP7A) P(1B)-type ATPase is a transmembrane copper-translocating protein. It contains six similar high-affinity metal-binding domains (MBDs) in the N-terminal cytoplasmic tail that are important for sensing intracellular copper and regulating ATPase function through the transfer of copper between domains. Molecular characterization of copper-binding and transfer is predominantly dependent on NMR structures derived from E. coli expression systems. A limitation of these models is the exclusion of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…In both experiments, correct trafficking to the plasma membrane and delivery to the basolateral membrane (in polarized MDCKs) upon copper stimulation was observed. These results are in line with previous observations that the phosphorylation site ATP7A:pT327 is not involved in aberrant trafficking of ATP7A ( Veldhuis et al, 2009 ), but is rather predicted to stabilize a conformational change in ATP7A, exposing the CxxC copper-binding region of MBD3, which might affect catalytic activity of ATP7A ( Veldhuis et al, 2011 ). This might indicate that catalytic activity, rather than aberrant trafficking of ATP7A, is responsible for the observed decrease in hepatic copper levels in Labrador retrievers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In both experiments, correct trafficking to the plasma membrane and delivery to the basolateral membrane (in polarized MDCKs) upon copper stimulation was observed. These results are in line with previous observations that the phosphorylation site ATP7A:pT327 is not involved in aberrant trafficking of ATP7A ( Veldhuis et al, 2009 ), but is rather predicted to stabilize a conformational change in ATP7A, exposing the CxxC copper-binding region of MBD3, which might affect catalytic activity of ATP7A ( Veldhuis et al, 2011 ). This might indicate that catalytic activity, rather than aberrant trafficking of ATP7A, is responsible for the observed decrease in hepatic copper levels in Labrador retrievers.…”
Section: Discussionsupporting
confidence: 92%
“…MBD3 is located in the cytoplasm and has the ability to receive copper from the Atox1 chaperone ( Strausak et al, 2003 ). MBD3 of ATP7A is only metallated in elevated copper conditions ( Banci et al, 2010 ) and is thought to be an important domain for regulating ATP7A activity via cell-signalling pathways ( Veldhuis et al, 2011 ). It has been shown that ATP7A:p.T327 is an important phosphorylation site of ATP7A ( Veldhuis et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…58 Recently, Veldhuis et al suggested, using MD simulations, that S339, which is in a loop facing the copper binding site, may facilitate the copper transfer process by exposing the CxxC copper binding region of MBD3 while copper-induced phosphorylation of T327 would stabilize this change in conformation. 59 In our simulations, Cys1 in Mnk3 apo is indeed largely solvent-exposed while Cys2 is completely buried, but the result is an exposed CxxC motif in Mnk3 holo (high g H in Table 4). The possibility of a low level of exposure of Cys2 to the solvent is supported by fluorescence labeling experiments by Yatsunyk et al on the MBDs of the related Wilson protein, showing that the cysteines of MBD3 were the least solventexposed.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 63%
“…Force field parameters can be generated using different methods. Bond, angle, or dihedral values are varied while we determine the energetics. The Hessian matrix using internal coordinates from frequency calculations can be utilized to compute the force constant values. Nonetheless, these two methods yield force field parameters depending on the choice of internal coordinates. Thus, different simulation results can be obtained using different choices in internal coordinates.…”
Section: Computational Chemistry Studies Of Transition Metal–aβ Compl...mentioning
confidence: 99%